PENGEMBANGAN CONTENT GOOGLE CLASSROOM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN DISPOSISI MATEMATIS SISWA SMK - Muhammad Haninul Fuad; Sugiatno Sugiatno; Yulis Jamiah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe development of information technology has an impact on human lifestyles in various fields. Practical learning without having to be complicated, can be done without space and time restrictions whenever and wherever, become the needs of students in the current digital era. Inevitably the teacher must answer the challenges of this era by innovating to develop or create creative learning media in accordance with the wants and needs of students. The purpose of this research is to produce product in the form of google classroom content whose design and development is theoretically feasible (based on expert validation), and is suitable for use in learning trigonometric material. This research is a research and development (R&D) study using the ADDIE model.The results of this study are the first Google classroom content meets the standards of eligibility and practicality based on the results of expert validator validation. After participating in learning by using the product of the development, students of SMK Negeri 4 Pontianak experienced an increase in the average ability of creative thinking and an increase in the average mathematical disposition.Keywords: google classroom content, mathematical disposition, mathematical creative thinking